Hydrolytic degradation and protein release studies of thermogelling polyurethane copolymers consisting of poly[(R)-3-hydroxybutyrate], poly(ethylene glycol), and poly(propylene glycol) - Loh, X.J. (2014)
10.1016/j.biomaterials.2007.05.016